Melting, Solidification, and Crystallization of a Thermoplastic Polyurethane as a Function of Hard Segment Content. Issue 11 (25th April 2019) - Stribeck, Almut; Eling, Berend; Pöselt, Elmar; Malfois, Marc; Schander, Edgar
Abstract: Thermoplastic polyurethanes (TPU) with varying hard segment contents (HSC) are monitored during melting and solidifying ( | T ˙ | = 20 K/min, T max = 220 ° C) by small‐angle and wide‐angle X‐ray scattering (WAXS and SAXS). Hard segments: MDI/BD. Soft segments: PTHF1000. The neat materials are injection‐molded, having small amorphous hard domains (chord length d ¯ h < 6 nm ). Results indicate complexity of morphology changes. For example, crystals are predominantly produced in freshly segregated, sufficiently large hard domains, while the temperature decreases slowly enough. After the thermal treatment, only the materials with HSC >∼ 35% show sharp Bragg peaks and larger hard domains ( d ¯ h > 7 nm ). When heated, small domains melt, but crystallization in the remaining large domains is not detected. Upon cooling, large agglomerates segregate first, which crystallize immediately. Segregation starts for HSC = 42% at 160 °C and for HSC = 75% at 210 °C. When HSC ≤ 30%, the morphologies before and after are similar, but afterward, many hard blocks are dissolved in the soft phase at the expense of the hard domain fraction. In heating and cooling the melts, multiple homogenization and segregation processes are observed, which are explained by the agglomeration of hard blocks of different lengths in the colloidal fluid. Abstract : Simultaneous SAXS and WAXS indicate that crystals are predominantly produced for hard segment contents (HSC) > 35% in freshly segregating, sufficiently large hard domains, while the temperature decreases slowly enough. For lower HSC, the thermal expansion coefficients of hard and soft phases appear to be similar.